Nitrogen management associated with growth retardants in wheat cv. Mirante (Revista de Ciências Agroveterinárias, 2014)
This study aimed to evaluate the nitrogen topdressing effects applied on vegetative cover and during the reproductive stage associated with associated with the use of reducing growth on plant height, yield and total protein content in grains of wheat cv. Mirante. The experiment was carried out at field conditions during 2011 growing season in Lages, SC. The experimental was a randomized block design with four replications in a 2x7 factorial, a total of 14 treatments consisted of twice nitrogen topdressing (vegetative and reproductive stage), six plant growth retardant treatments (mepiquat chloride, chlormequat chloride, chlorocholine chloride, ethyl-trinexapac, prohexadione-Ca and ethepon) and two doses of retardant. The plants that received N at vegetative received a dose of plant growth retardants used in stage 31 of Zadoks, and plants that received N at vegetative + reproductive also received two doses of retardants applied in stages 31 and 32 of Zadoks (first and second node visible). The treatments with ethyltrinexapac or prohexadione-Ca, allowed the plant height reduction of at least 10 cm and did not affect the characteristics: number of spikelets per spike, grains diameter higher than 1.75 mm, thousand grain weight and hectoliter mass. The N topdressing at reproductive stage of wheat allowed increase in total protein content from 12.2 to 13.9%. There were no differences in yield between the times of nitrogen applied nor due to plant growth retardant doses, with an average yield of 4,750 kg ha-1. However, related to the aspects of grain quality, it was observed that N topdressing at reproductive stage of crop lead to high grain quality, high grain specific mass and to high total protein content.
Keywords: Triticum aestivum; Plant growth regulators; Plant nutrition.